2019
DOI: 10.1177/1461445619829236
|View full text |Cite
|
Sign up to set email alerts
|

Managing epistemic imbalances in peer interaction during mathematics lessons

Abstract: In this study, we investigated how students manage their lack of/insufficient understanding of the content of a mathematical task with the aim of reaching shared understanding and epistemic balance in peer interaction. The data consist of recordings collected during a mathematics project (6 × 75 minutes) in a Finnish lower secondary school. The findings, drawing on conversation analysis, showed two markedly different sequence trajectories: (1) how interaction between a K+ and a K− (more/less knowledgeable) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Authors in the field argue that when students were able to check their own results and correct their own procedures, they became more independent from a pedagogical perspective, increasing their autonomy and requiring less support from their teachers or instructors [78][79][80]. The fact that students could associate different mathematical concepts in a more complex way is rational considering that these associations were promoted in three ways (teacher's explanations, peer's help, and analytical and graphical developments of the digital tools) instead of just the one way (teacher's explanations) of traditional learning [81][82][83][84]. Finally, the fact that students in the experimental group did more exercises and problems than those in the control group may be attributable to two main factors: the helping behaviour that usually arises during peer tutoring interactions [85][86][87][88] and the instant feedback provided by the digital tools [89][90][91].…”
Section: Discussion For Research Question 2: Effects On Way Students ...mentioning
confidence: 99%
“…Authors in the field argue that when students were able to check their own results and correct their own procedures, they became more independent from a pedagogical perspective, increasing their autonomy and requiring less support from their teachers or instructors [78][79][80]. The fact that students could associate different mathematical concepts in a more complex way is rational considering that these associations were promoted in three ways (teacher's explanations, peer's help, and analytical and graphical developments of the digital tools) instead of just the one way (teacher's explanations) of traditional learning [81][82][83][84]. Finally, the fact that students in the experimental group did more exercises and problems than those in the control group may be attributable to two main factors: the helping behaviour that usually arises during peer tutoring interactions [85][86][87][88] and the instant feedback provided by the digital tools [89][90][91].…”
Section: Discussion For Research Question 2: Effects On Way Students ...mentioning
confidence: 99%
“…Recent CA research has examined the role of knowledge in the organisation and structure of a range of interactions (Heinemann et al, 2011;Heritage, 2012bHeritage, , 2012aHeritage & Raymond, 2005Kämäräinen, Björn, Eronen, & Kärnä, 2019;Keevallik, 2011;Raymond & Heritage, 2006;Stivers, Mondada, & Steensig, 2011). Their analysis often focuses on how different participants may orient to differences in what people do or do not know, or claim to know (or not know).…”
Section: A Ca Approach To the Study Of Epistemicsmentioning
confidence: 99%
“…Jakonen, 2014;Sert & Walsh, 2013), but some recent works within mathematics education (e.g. Kämäräinen et al, 2019;Koole, 2012aKoole, , 2012b illustrate the negotiation of epistemic access and responsibilities as described below.…”
Section: A Ca Approach To the Study Of Epistemicsmentioning
confidence: 99%
“…This may contribute to our understanding of how intersubjective orientations are shaped in writing practices in school settings and generate new insights into the role of epistemics within this dialogic context (Alexander 2008;Wegerif 2011) that aims at reaching shared understanding of a task, sharing ideas, and supporting and encouraging each other to contribute and to value all contributions (Littleton and Mercer 2010;Mercer and Littleton 2013;Rojas-Drummond et al 2020;Vrikki et al 2019). CA-informed studies on epistemics in student-student interaction have shown the role of epistemic positioning in the social organisation of an event and in reaching shared understanding between participants (Back 2016;Heller 2018;Kämäräinen et al 2019;Melander 2012). A relatively large proportion of the studies paid attention to how these trajectories are shaped by initial actions that convey a less knowledgeable (K-) position, for instance how epistemic work is steered and leads to resolving emerging knowledge gaps or epistemic asymmetry by information requests to mobilise help from a peer (Jakonen and Morton 2015;Melander Bowden 2019), by sequential patterns of help-seeking interactions (Svahn & Melander Bowden 2019), or by polar and wh-interrogatives (Kämäräinen et al 2019).…”
Section: Dimensions Of Knowledge In Interactionmentioning
confidence: 99%
“…CA-informed studies on epistemics in student-student interaction have shown the role of epistemic positioning in the social organisation of an event and in reaching shared understanding between participants (Back 2016;Heller 2018;Kämäräinen et al 2019;Melander 2012). A relatively large proportion of the studies paid attention to how these trajectories are shaped by initial actions that convey a less knowledgeable (K-) position, for instance how epistemic work is steered and leads to resolving emerging knowledge gaps or epistemic asymmetry by information requests to mobilise help from a peer (Jakonen and Morton 2015;Melander Bowden 2019), by sequential patterns of help-seeking interactions (Svahn & Melander Bowden 2019), or by polar and wh-interrogatives (Kämäräinen et al 2019). In our study, we will focus on the perspective of 'being knowledgeable' (K+), by analysing how 'I know', 'you know' and 'we know' are used in sequences of peer talk.…”
Section: Dimensions Of Knowledge In Interactionmentioning
confidence: 99%